Data on First Record of Brown Morph Banded Langur (Presbytis femoralis), Leucistic Dusky Leaf Monkey (Trachypithecus obscurus) in Malaysia and Review of Morph Diversity in Langur (Colobinae) - Mohd Faudzir, Najmuddin; Hidayah, Haris; Nursyuhada, Othman; Fatin, Zahari; Mohd Ridwan, Abd Rahman; Badrul Munir, Md Zain; Rohani, Shahrool Annuar; Othman, Ayeb; Iqramullah, Othman; Muhammad Abu Bakar, Abdul-Latiff (Elsevier Inc., 2020)
Morphism refer to polymorphic species, in which multiple colour variants coexist within a population. Morphism in primates is common and langurs also exhibit certain characteristics of morphism, such as conspicuous natal coats. Banded langurs (Presbytis femoralis) and dusky leaf monkey (Trachypithecus obscurus) exhibits the same characteristics of conspicuous natal coats, but these coats are only limited to infants and changed when they reached adulthood. This article reports the first discovery of rare brown morph of two adult male banded langurs and one leucistic adult female dusky leaf monkey in Malaysia.